2011
DOI: 10.1074/jbc.m111.255737
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroperoxy-2-nonenal Is Not Just an Intermediate but a Reactive Molecule That Covalently Modifies Proteins to Generate Unique Intramolecular Oxidation Products

Abstract: ␣,␤-Unsaturated aldehydes generated during lipid peroxidation, such as 4-oxoalkenals and 4-hydroxyalkenals, can give rise to protein degeneration in a variety of pathological states. Although the covalent modification of proteins by these end products has been well studied, the reactivity of unstable intermediates possessing a hydroperoxy group, such as 4-hydroperoxy-2-nonenal (HPNE), with protein has received little attention. We have now established a unique protein modification in which the 4-hydroperoxy gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 28 publications
4
19
0
Order By: Relevance
“…6). Our data suggested that oxidative cleavage of the C3-C4 bond in HPNE occurred during incubation to produce MDA, as reported previously [31].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…6). Our data suggested that oxidative cleavage of the C3-C4 bond in HPNE occurred during incubation to produce MDA, as reported previously [31].…”
Section: Discussionsupporting
confidence: 72%
“…EDE can also form Michael addition products with His [30]. Although HPNE is a direct precursor of ONE and HNE, it is reported that it can modify Lys to generate adducts of unusual structure through a mechanism involving hydroperoxy group-mediated intramolecular oxidation [31].…”
Section: Introductionmentioning
confidence: 99%
“…However, these signalling processes most probably involve its reaction and adduct formation with signalling proteins, thus altering their activity (usually inhibition), rather than reversible ligand binding [45]. Interestingly, it appears that hydroperoxynonenal is not just a reactive intermediate leading to HNE, but also has biological effects in its own right, as it has been reported to modify proteins [46].…”
Section: Alkanalsmentioning
confidence: 99%
“…However, t -butylhydroperoxide is used in synthesis reactions to peroxidize imine bonds, which then lose water to form the amides, so we speculate that similar reaction would occur with lipid peroxides. A similar type of reaction from imine to amide has been proposed during the reaction of 4-hydroperoxy-nonenal with lysine to form N -4-hydroxy-nanenoyl-lysine (Shimozu et al, 2011). Thus the aldehydes formed during fragmentation such as hexanal and 8-oxo-octaenoate-PC could react with PE to initially form an imine bond, and then peroxidation of this bond by LOOH would rationalize the formation of N -hexanoyl-PE and N -C7:1CA-PE, respectively (Fig 22).…”
Section: Class Iv: Oxidatively N-modified Phospholipids (Pl)mentioning
confidence: 72%